Locked plating of geriatric olecranon fractures leads to low fixation failure and acceptable complication rates - Kelsey L. Wise, MD; Sarah Peck, BS; Lauren Smith, MD; Chad Myeroff, MD (JSES International, 2021)
Hypothesis: The purpose of this study was to report the rate of major complications in patients with geriatric olecranon fractures managed operatively with a locking plate. Secondary objectives included minor complications, as well as pain and range of motion at the final follow-up. We hypothesized that these patients have a low rate of complications as well as low pain and satisfactory elbow range of motion at the final follow-up. Materials and Methods: A retrospective review of isolated geriatric olecranon fractures presenting from 2006 to 2019 was performed at a single level I trauma center. Inclusion criteria were ≥75 years of age, operative management with a locking plate, and clinic follow-up at least until evidence of radiographic union or a major complication. Exclusion criteria included nonoperative management, insufficient follow-up, and absence of locking plate in surgical technique. Variables examined included demographic information, Charleston comorbidity index, American Society of Anesthesiologists score, living independence, gait assistance, mechanism of injury, open vs. closed fracture, Mayo radiographic classification, Arbeitsgemeinschaft für Osteosynthesefragen classification, time to surgery, implant type, presence of triceps offloading suture, length of postoperative immobilization, date of radiographic union, range of motion at the final follow-up, pain visual analog scale score at the final follow-up, major and minor complications, and return to the operative room. A major complication was defined as a return to the operative room for deep infection or loss of fixation (displacement of fracture >5 mm). A minor complication was defined as any other complication. Results: A total of 65 patients ≥75 years of age with olecranon fractures were identified. Of these, 36 patients met inclusion criteria with an average follow-up of 23 weeks (range 5-207). The mean length of immobilization was 13 days (range 0-29 days). Thirty-two of 36 (88.8%) patients achieved radiographic evidence of union at an average of 8.9 weeks (range 5.3-24.1 weeks). There were 4 remaining patients who underwent secondary intervention before primary union representing an 11.1% major complication rate including 2 deep infections (5.6%) and 3 failures of fixation (8.3%). There were 7 minor complications in 5 of 36 (13.9%) patients. At the final follow-up, the average visual analog scale score was 2.6 (range 0-6), the average elbow arc of motion was 120° (range 70-147°), and mean pronation/supination was 85°/84° (range 45-90°/45-90°). Conclusion: Geriatric olecranon fractures are a challenging orthopedic problem with remaining controversy regarding ideal treatment. Despite advancement in geriatric fracture care, there is scant literature on the outcomes of locked plating technology in geriatric olecranon fractures. This study supports use of operative anatomic fixation with precontoured locked plates and early mobilization with an acceptable failure rate.